SPECIALIZED FUNCTIONAL PROPERTIES OF MUSCULAR ACTIVITY ENERGY SUPPLY SYSTEM OF HIGHLY SKILLED CYCLISTS OF DIFFERENT SPECIALIZATION - Kolumbet, A. N.; Paryshkura, Yu. V. (Rehabilitation and Recreation, 2024)
Purpose is to analyze the functional features of the body energy supply system, which are specific to high levels of special work capacity in cycling. Material and methods. In total 44 highly skilled cyclists were examined: 16 athletes specializing in road team racing, 12 athletes specializing in 4000 m pursuit, 9 athletes specializing in 1000 m time trial, and 7 athletes specializing in sprint. The studies were conducted in 2017–2019. A complex methodology for determining the level of functional fitness was used. It included the registration of the main parameters of gas exchange, external respiration, blood, and cardiovascular system at different loads. Results. The highest values of MOC (70.2±0.63 ml.min.kg-1), VC (6985±5.219 ml), maximum minute volume of blood circulation (36.6±0.37 l.min.-1), systolic volume (201.5±5.17 ml), the amount of oxygen transported by arterial blood (91.7±4.06 ml.min.kg-1 of body weight), lung diffusion capacity at MOC (102.5±2.96 ml.min.-1, mmHg), and some other indices were registered in road racers. Cyclists specialized in sprint and time trials were distinguished by the highest values of CO2 excretion rate at supercritical working efficiency, “alactate” and “lactate” power, high ratio of ventilation and circulation to gas exchange. In addition, they had the highest buffer capacity (51±0.7 meq.l-1), sensitivity to CO2 (34.4±3.92 ml.min.-1 mmHg.kg-1), and the rate of rapid CO2 storage (98 ml.min.-1, mmHg). The values of MOC in sprinters (54.8±1.21 ml.min.kg-1) were significantly lower than in cyclists specialized in time trials (62.6±0.86 ml.min.kg-1) and pursuit (67.3±1.05 ml.min.kg-1). Conclusions. Specialization in different types of cycling races significantly affects both the work capacity in tests and the dynamics of the maximum manifestations of the indices of gas exchange, external respiration, blood circulation, blood gas transport, and changes in the body internal milieu. The economy of functional responses during the work of critical power is higher in road racers and cyclists specialized in pursuit. The highest level of aerobic power development is observed in road racers, whereas the lowest value of this index is characteristic of sprinters. The highest value of anaerobic power is noted in athletes specialized in time trials, whereas the ability to explosive energy expenditure is peculiar for sprinters.